Design and optimisation of three-phase salient rotor wound field flux switching motor - Khan, Faisal (2016)
Permanent magnet-free wound field flux switching machine (WFFSM) with a segmented rotor and non-overlapping windings is an attractive alternative for driving high torque density applications due to their low cost, high efficiency, high average torque and power. However, a rotor with segments makes the motor less robust and difficult to be assembled, while WFFSM with salient rotor and overlapping windings inherit high copper losses and less efficiency due to their long end-windings. This thesis deals with a novel structure of WFFSM employing a salient rotor with nonoverlapping field and armature windings on the stator and a presentation of an unexcited rotor. The non-overlapping winding arrangement on the stator consumes less copper material, thus improves the efficiency. Moreover, the salient rotor structure with high mechanical strength is suitable for high-speed operation. The design restrictions and specifications of the proposed motor are keep similar as WFFSM with a segmented rotor. The JMAG-Designer ver.14.1 was used to verify the motor’s operating principle and performance characteristics. Three-phase configurations of WFFSM with non-overlap windings and salient rotor were studied, from the design features to performance analysis. For the three-phase operation, 11 topologies were feasible when employing a 12-tooth and 24-tooth stator. The subsequent optimisation work carried out using deterministic optimisation approach and Genetic Algorithm (GA) method to achieve the target average torque of 25.8 Nm and power of 6.49 kW. Designed and analysed by 2D and 3D finite element analysis (FEA), the optimised 12S-10P configuration had achieved high torque and power of 4.6% and 4.8% respectively, as compared to 12S-8P WFFSM with segmental rotor and non-overlapping windings. Moreover, the torque and power of the optimised design were also greater than 12S-8P WFFSM with salient rotor and overlapping windings. The 12S-14P topology had produced high average torque and power at low armature and field currents compared with all designs.